Relativistic interactions for meson-nucleon systems: applications in the theory of nuclear reactions - Shebeko, A.V.; Frolov, P.A.; Dubovik, E.A. (Вопросы атомной науки и техники, 2012)
It is shown that the method of unitary clothing transformations (UCT) developed in [1, 2] and applied to nuclear physics problems [3, 4], gives a fresh look at constructing interactions between the "clothed'' nucleons, these quasiparticles with the properties of physical nucleons. Показано, что метод унитарных одевающих преобразований (УОП), развитый в работах [1,2] и применённый к задачам ядерной физики [3,4], позволяет по-новому взглянуть на построение взаимодействий между "одетыми'' нуклонами, этими квазичастицами со свойствами физических нуклонов. Показано, що метод унітарних одягаючих перетворень (УОП), розроблений в працях [1,2] та застосований до задач ядерної фізики [3,4], дозволяє по-новому поглянути на побудову взаємодії між "одягненими'' нуклонами, цими квазічастинками з властивостями фізичних нуклонів.